Controlling Offensive Behavior Using Narrative Exposure Therapy: A Randomized Controlled Trial of Former Street Children. (March 2015) - Crombach, Anselm; Elbert, Thomas
Insecure and violent environments foster two different forms of aggressive behavior: reactive aggressive responding, such as fearful or angry impulsive behavior to perceived threats, and appetitive aggression, which encompasses violence-related feelings of power, excitement, and pleasure. We tested whether forensic offender rehabilitation narrative exposure therapy (FORNET; five sessions) would reduce involvement in everyday violence and produce beneficial effects for mental and physical health. In a Burundian residential center for former street children, we identified a subset of 32 male youths (mean age = 17 years) who scored highly in appetitive aggression. We conducted a randomized controlled trial by assigning matched pairs to receive either FORNET or treatment as usual. During the follow-up (4–7 months after completing treatment), the 16 youths who received FORNET reported having committed significantly fewer offenses (Hedges's g = 0.62) and presented with fewer physical-health complaints (Hedges's g = 0.56) than did their matched control participants.